Past, Present and Future of Agroforestry Systems in Europe (Agroforestry - The Future of Global Land Use SE - 16, 2012)
Many traditional land-use systems in Europe involved agroforestry in the pre-industrial era, but, over the years, increased mechanization led to the develop- ment of increasingly specialized crop, animal and wood production systems. As a consequence, the area under agroforestry declined in many regions of Europe, and agroforestry systems became con fi ned to situations where understorey primary production is restricted due to cold temperatures (Boreal and Alpine areas) or drought (Mediterranean areas) and to plots that are hard to reach or too small for cultivation with modern machinery, as in Spain, Italy and the lower altitude mountain regions in southern and central Germany. On the whole, agroforestry continued to be practised only where it enabled farmers to obtain economic returns from lands that were otherwise relatively unproductive and mostly limited to silvopastoral practices. Since the mid-1990s, however, European policies have encouraged land management systems that combine production, environmental services (biodiversity, carbon sequestration, nutrient cycling and water quality) and social bene fi ts, and this has created a new interest in agroforestry systems. Today, the major agroforestry practices in Europe include silvopasture and silvoarable. However, the bene fi ts and opportunities offered by agroforestry can only be realized with substantial investments and coordinated efforts in research, education, knowledge transfer and appropriate national policies across Europe.

Silvopastoral systems in Portugal: Current status and future prospects (Agroforestry in Europe: Current Status and Future Prospects., 2008)
Portugal has a high diversity of agroforestry systems like other Mediterranean countries. This is the result of the Mediterranean climate, great variability of bioclimatic conditions, a long history of land use, and a marked variation in land tenure between north and south of the country. Four major silvopastoral systems are described: two classically Mediterranean – montado and Olive tree system, and two typically of the transitional environment between Mediterranean and Temperate conditions – Pyrenean oak and Chestnut systems. Some products of traditional agroforestry systems such as charcoal, organic manure, livestock production and others have become less valuable with the socio-economic transformation of the 1960s. These systems have been declining from approximately 1950 onwards. Currently, the focus on sustainable agriculture, with greater emphasis on nature and landscape conservation, has meant that environmental values now represent new opportunities for income generation from these systems. A better understanding of traditional agroforestry systems is needed for the formulation of a specific European policy that will preserve European landscapes. This paper looks at the future potential for silvopastoral systems in Portugal based on current status.

Soil nutrient status and forage yield at varying distances from trees in four dehesas in Extremadura, Spain (Silvopastoralism and Sustainable Land Management: Proceedings of an International Congress on Silvopastoralism and Sustainable Management Held in Lugo Spain, in April 2004, 2006)
The aim of this study was to understand the effect of holm-oak (Quercus ilex) on the soilnutrient concentration and its consequence on the yield of understory forage (Avena sativa) in four dehesas of CW-Spain. The soils of the dehesas varied in soil fertility (chromic Luvisols and Achrisols, and eutric Leptosols). Forage dry-matter yields were determined from 1-m2 sample plots at distances ranging from 2 to 20 m from the tree (9 trees per farm and year). Soil samples (0-30 cm depth) were also collected from the same sampling locations, and were analysed for pH, Electrical Conductivity, organic C, CEC, total-N, available N and base cations. Soil analysis results showed that the most of the values increased in the vicinity of the tree: organic C, total-N, CEC and exchangeable Ca2+ and K+. Differences in forage yield were mainly explained by fertilization dosage, light availability (estimated from Montero and Moreno, 2004) and soil CEC. In more fertile soils, forage production was negatively effected by the presence of the trees, as a consequence of light reduction (Competence), while in more oligotrophic soils, forage production was positively affetced by trees (Facilitation).